Effect of B4C and graphite particulates on the mechanical and micro structural characteristics of AA 5052 hybrid composites. (2020) - Kiran, K.; Ravikumar, K.; Sree Balaji, V.S.
Abstract: Reinforced aluminium metal matrix composites are being applied in various fields like automobile, aerospace and other industries. In this study the mechanical behavior of aluminium alloy (AA 5052) composites reinforced with boron carbide and graphite are studied. Aluminium matrix composite specimen was prepared by adding 2, 4, 6, and 8% of boron carbide and graphite by stir casting process. The composites were subjected to tensile, hardness and elongation studies. Scanning Electron Microscopy (SEM) was employed to analyze the uniform distribution of boron carbide and graphite of in the aluminium matrix metal. The microphotographs of the composites specimen exposed fairly uniform distribution of boron carbide and graphite particles in composites. Addition of B4 C and graphite in aluminium matrix exhibited better mechanical properties and can be used as a possible material in marine, offshore and other industrial applications.